Epoxidation of Multi‐Walled Carbon Nanotubes by Organocatalytic Oxidation12. Issue 14 (31st March 2015) - Annese, Cosimo; D'Accolti, Lucia; Armuzza, Valentina; Da Ros, Tatiana; Fusco, Caterina
Abstract: Even though many functionalization methodologies for covalent modification of carbon nanotubes (CNTs) have been proposed, mild but effective approaches are still needed. Here we describe the epoxidation of multi‐walled carbon nanotubes (MWCNTs) with dioxirane for an environmentally friendly oxidation process with an organocatalyst. Thank to the choice of dioxiranes (accessible and easy to handle and to store), multiple oxidation cycles could be performed on the same sample, thus allowing for a final improvement in the degree of oxidation at the CNT sidewall. The obtained derivatives were then used as electrophilic platforms for successive modification with an amine, with a high degree of functionalization (about 750 μmol g –1 from TGA analysis) being obtained. Abstract : An efficient method for the epoxidation of multi‐walled carbon nanotubes (MWCNTs) is proposed. It leads to the production of materials that can be easily further functionalized by nucleophiles. Complete chemical (TGA, FTIR, XPS, Raman) and morphological (TEM) characterization of the materials has revealed a high degree of functionalization.